Gene expression analysis of neuropeptides in oral mucosa during periodontal disease in non‐human primates. Issue 7 (20th July 2018) - Ferrin, John; Kirakodu, Sreenatha; Jensen, David; Al‐Attar, Ahmad; Peyyala, Rebecca; Novak, M. John; Dawson, Dolph; Al‐Sabbagh, Mohanad; Stromberg, Arnold J.; Orraca, Luis; Gonzalez‐Martinez, Janis; Burgos, Armando; et al.
Abstract: Background: Neuropeptides (NPs) are innate pivotal regulators of the immunoinflammatory response. Nevertheless, their role in the pathogenesis of periodontal disease remains unknown. Changes in gene expression of 10 NPs and 16 NP receptors (NPRs) coincident with the initiation, progression, and resolution of periodontitis were determined. Methods: The ligature‐induced periodontitis model was used in rhesus monkeys (n = 18). Gingival tissue samples were taken at baseline (preligatures), at 2 weeks and at 1 month (initiation), and at 3 months (progression) postligation. Ligatures were removed and samples taken 2 months later (resolution). Total RNA was isolated from tissues and NP/NPR gene expression microarray analysis was performed. Gene expression changes were validated by quantitative polymerase chain reaction and immunohistochemistry. Results: Unexpectedly, the expression of pro‐inflammatory NPs/NPRs did not change during periodontitis or with resolution. However, increased expression of the anti‐inflammatory NPs adrenomedullin (ADM) and galanin (GAL), and the NPRs calcitonin receptor‐like (CALCRL) and receptor activity‐modifying protein‐2 and ‐3 (RAMP2 and RAMP3) were observed during initiation and progression of disease. The expression of the same NPs/NPRs exhibited a significant positive correlation with both molecular (interleukin‐1ß, matrix mettaloproteinase‐9, and receptor activator of nuclear factor‐kappa B ligand) and clinical measures of gingival inflammation and tissue destruction. Conclusion: Initiation and progression of periodontitis involve significant overexpression of ADM, GAL, CALCRL, RAMP2, and RAMP3. These anti‐inflammatory NPs/NPRs could play a role in the unresolved infection and inflammation that normally drives tissue destruction in periodontitis. Both ADM and GAL potentially are new candidates to consider as biomolecules associated with periodontal disease activity.